(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this work, complex structures are considered, we build two bases: RA -basis and A - basis. We also define an almost complex structure and its adjointG -structure. We define locally the Nijenhuis tensor of an almost complex structure, prove that this tensor is defined globally, and obtain an explicit expression for this tensor.